"n Narratief vir kerk-wees vandag - Merwe, J. Christo van der (HTS teologiese studies, 2014)
A narrative of church life today. We live in a time when survival seems to be the biggest concern of most mainline congregations and denominations. How can the church possibly survive? This is a question that is asked in almost every corner of the institution. Since the 1960s, numerous books and articles have been published, trying to get a handle on why the mainline churches are in decline. Whatever the cause may be, decline is causing great fear and anxiety in the mainline churches. In an effort to answer the underlying question: ‘What shall we do to turn the situation around?’, some churches are simply trying to ‘market’ themselves and their message. Others try to ’do’ church differently. Some try to rediscover the purpose of the church, et cetera. Cheryl Peterson argues that churches are, in fact, facing an ecclesial crisis, that is much more than a crisis of declining numbers and membership. There is a deeper and more basic issue that must be explored, one that has to do with the church’s theological identity, and that is: what it means to be church? This article is about the question: Who is the church? And it answers the question on the basis of Peterson’s thesis by means of a narrative of the church that commences with the Spirit.